HTML & CSS video how-to - Meloni, Julie C.; Safari eBooks ([Place of publication not identified] : Sams, 2015)
"HTML & CSS Video How-To is a series of short, 2- to 5-minute how-to videos that walk you through a specific task or technique related to creating web pages with HTML and CSS. Adapted from Julie C. Meloni's book Sams Teach Yourself HTML and CSS in 24 Hours, each video is self-contained and focused entirely on one particular task. You can either go through the videos in sequence or you can jump into a particular task, see how something is done, and then jump out again."--Resource description page.
Title from resource description page (viewed December 14, 2015).
Presenter, Julie C. Meloni.
Keywords: HTML (Document markup language); XHTML (Document markup language); Cascading style sheets; Web site development; Electronic books